Gambaran Penyimpanan Obat di Apotek X Kota Pekalongan - Andre Kurniawan; Khafid Mahbub (CV. ITTC INDONESIA, 2025)
The storage of pharmaceutical supplies is an essential activity in the management of medicines in pharmacies, aiming to maintain the quality, stability, and safety of drugs. This study aimed to assess the compliance of pharmaceutical storage practices in a pharmacy with applicable standards. The research used a descriptive approach through direct observation of facilities, procedures, and storage systems. The results showed that most storage activities were in accordance with standards, such as drug arrangement in alphabetical order, the application of FIFO and FEFO methods, and maintaining cleanliness in the storage area. However, several aspects still need improvement, including the absence of thermometers and temperature recording cards in refrigerators, as well as the lack of separation and special labeling for LASA and High Alert medications. In conclusion, the pharmaceutical storage practices in the pharmacy were generally good, but improvements are needed in monitoring high-risk drugs and temperature control to ensure the quality and safety of medicines.